Piat' peterburgskikh portretov . Piat' peterburgskikh portretov . Five Petersburg Portraits . Пять петербургских портретов - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. Interviews with young musician Vladimir Lanne, with young farmer Aleksandr Khrustalev; with young artist Oleg Kulikov; with businessmen Mikhail Zlydnikov; and the ballerina Elena Chubarova. Contributors: Vitukhnovskii, Vladimir (Director) Интервью с молодым музыкантом Владимиром Ланнэ, молодым фермером Александром Хрусталевым; молодым художником Олегом Куликовым; предпринимателем Михаилом Злыдниковым; ,балериной Еленой Чубаровой. Создатели: Витухновский, Владимир (Режиссер)